1984
DOI: 10.1007/bf00056767
|View full text |Cite
|
Sign up to set email alerts
|

A karyological study of Accipitridae (Aves: Falconiformes), with karyotypic descriptions of 16 species new to cytology

Abstract: Karyotypic descriptions are given of 16 species of Accipitridae new to cytology, viz. Torgos tracheliotus. For reasons of comparison the karyotypes are included of 5 species that have been previously studied, viz. Gypaetus barbatus, Haliaeetus albicilla, H. leucocephalus, H. vocifer and Pernis apivorus. All these species share the typical characteristics of the accipitrid karyotype, a moderate diploid number (66-72), the absence of large macrochromosomes, the presence of only 6-12 microchromosomes and a high n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0

Year Published

1984
1984
2008
2008

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(47 citation statements)
references
References 13 publications
2
45
0
Order By: Relevance
“…In particular our study showed interspecies DNA content differences among the studied cases, especially evident in the Falconiformes, confirming data in the literature. In fact, previous studies with cytogenetic analysis (3,4,14) and with static cytometry (19) have revealed substantial difference, in genome constitution, particularly among the species belonging to the Falconiforrnes and, within the Strigiformes, between the two families of Strigidae and T ytonidae. Such variability involves both the chromosome diploid number (2x1) and the nuclear DNA content (pginucleus).…”
Section: Discussionmentioning
confidence: 99%
“…In particular our study showed interspecies DNA content differences among the studied cases, especially evident in the Falconiformes, confirming data in the literature. In fact, previous studies with cytogenetic analysis (3,4,14) and with static cytometry (19) have revealed substantial difference, in genome constitution, particularly among the species belonging to the Falconiforrnes and, within the Strigiformes, between the two families of Strigidae and T ytonidae. Such variability involves both the chromosome diploid number (2x1) and the nuclear DNA content (pginucleus).…”
Section: Discussionmentioning
confidence: 99%
“…In Accipitridae (Falconiformes), chromosome fusions involving microchromosomes have produced small-and/or medium-sized metacentric chromosomes, with a consequent decrease in the diploid number (De Boer, 1975;De Boer and Sinoo, 1984). In the Ciconiidae, however, microchromosome reduction was not followed by an increase in the number of macrochromosomes, and apparently resulted in loss of microchromosomes (Belterman and De Boer, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…However, the karyotype of the common ancestor of extant sauropsids is thought to have contained both macrochromosomes and microchromosomes (Burt 2002;Norris et al 2004), although some lineages underwent frequent secondary fusion of microchromosomes resulting in no or few microchromosomes as seen in the reptilian family Crocodylidae and the avian family Falconiformes (Cohen & Gans 1970;De Boer & Sinoo 1984). In contrast, chromosome sizes are relatively uniform and there is no striking bias in inter-chromosomal GC-content in most mammals.…”
Section: Insight Into the Evolutionary History Of Intra-genome Gc Hetmentioning
confidence: 99%